If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 12 + x = 0 Reorder the terms: 12 + 3x + x = 0 Combine like terms: 3x + x = 4x 12 + 4x = 0 Solving 12 + 4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 4x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + 4x = 0 + -12 4x = 0 + -12 Combine like terms: 0 + -12 = -12 4x = -12 Divide each side by '4'. x = -3 Simplifying x = -3
| 2x+9-x=8+2x-6 | | F(t)=sin(2t) | | 2(3+5x)-4=62 | | -7(9a-4)=31 | | 17s=18s-3 | | 4y+5=3y-4 | | 6x+12y=8 | | 2x-g=7 | | 0.25(84-32n)-n= | | g+4=2g-6 | | 9+12+16= | | 3g-11(-1)=14 | | -3-2x=-3 | | g=2(-1)+3 | | 07(h+2)+1.6=17 | | 3x^2(x-3)=0 | | 57-(5x+15)=5(x+4)+x | | y=2(3y-5)-8 | | (8x+2y)(5x-4y)= | | -20+x=-2x+43 | | .33q=q | | Log(8x+4)=1+log(x+1) | | 5(sat+s)=14a-29 | | x-3=-x-5 | | 7+n=12-3 | | -y-8-y=0 | | 520x+1104=3029+345x | | 2(-2x-3)=4x-6 | | Log(8x+4)=log(x+1) | | 9x^2=30x-17 | | (5p^2-3)=(2p^2-3p^3) | | 520x+1104=3029+345 |